Strengthening the social competence of lecturers and students through the principle of religious moderation within the framework of MBKM policy - Suwantoro, Suwantoro; Ummah, Fiena Saadatul; Ubaidillah, Mohammad Farah (IAIN Salatiga, 2023)
This research is focused on the importance of efforts to strengthen the social competence of lecturers and students in the university environment. More specifically, this study emphasizes the urgency of the principle of religious moderation in enhancing the social competence of lecturers and students, in line with the curriculum policy of independent learning and independent campus (MBKM). As a new paradigm in the world of education, MBKM provides students with the freedom to learn with the aim of creating an inclusive learning environment that is relevant to the needs and demands of the workforce. Through a literature review and qualitative analysis using the Miles Huberman interactive data analysis, which includes three main steps: data condensation, data display, and conclusion/verification, the results indicate that the principles of religious moderation, such as Tawassuth (taking the middle path), Tawāzun (balance), I'tidāl (straightforwardness and firmness), Tasāmuh (tolerance), Musāwah (egalitarianism), and Syurā(consultation), contribute to strengthening the social competence of lecturers and students in implementing the independent curriculum policy. This research provides conceptual insight into creating an inclusive university environment in a diverse society by adopting the principles of moderation. Creating such conditions will make it easier to implement MBKM policy programs.